S140 BMPR-II deficiency leads to an increase in egg deposition and cytokine release in the lungs of mice chronically infected with schistosomiasis. (14th November 2013) - Crosby, A; Soon, E; Jones, F; Southwood, M; Haghighat, L; Toshner, M; Raine, T; Horan, I; Yang, P; Davenport, A; Dunne, DW; Morrell, NW
Abstract : Rationale and Objectives: Schistosomiasis is the world-wide leading cause of pulmonary arterial hypertension (PAH) and is particularly prevalent in the third-world. More than 80% of patients with PAH in the western world have a mutation in bone morphogenetic protein type-II receptor (BMPR-II), which is a member of the transforming growth receptor-beta (TGF-b) superfamily and is important in cell proliferation and differentiation. The aim of the study was to determine if mice with a heterozygous null mutation in BMPR-II are more susceptible to schistosomiasis–induced PAH, compared to wild-type littermates. Methods: Wild-type and mutant C56/BL6 mice were infected percutaneously with a low dose of S.mansoni . Non-infected WT and MUT mice were also studied. At 17 weeks post-infection right ventricular systolic pressure (RVSP) and right ventricular (RV) hypertrophy, liver and lung egg counts and body weight were measured. Pulmonary vascular remodelling and liver histology were assessed by morphometry, following immunohistochemistry. Micro-CT was performed to determine egg deposition. A macrophage phagocytosis assay was also performed. Measurements and Main results: At 17 weeks post-infection there was no significant difference in RVSP, the degree of RV hypertrophy, mean area of liver vasculature, mean number of liver vessels or liver weight between infected BMPR-II + / + and BMPR-II +/- mice. However, there was a significant reduction in body weight, a significant increase in lung egg deposition and lung cytokine expression in the BMPR-II +/- mice compared to the wild-type mice 17 weeks post-infection. There was no significant difference in serum or liver cytokine levels. We saw a significant increase in pulmonary vessel wall thickness in both BMPR-II + / + and BMPR-II +/- mice infected mice, compared to their respective non-infected controls. There was no difference in the ability of macrophages from BMPR-II + / + and BMPR-II +/- mice to phagocytose fluorescently tagged beads. Conclusions: This study has shown that BMPR-II mutations do not predispose to schistosomiasis-induced PAH, but that there is an increased ability of the eggs to gain access into the lungs and a subsequent heightened inflammatory response. This appears not to be due to an innate difference in the liver vasculature or a defect in egg clearance by macrophages.